A rationale multidisciplinary approach for treatment of esophageal and gastroesophageal junction cancer: Accurate review of management and perspectives. (December 2018) - Chiappa, Antonio; Andreoni, Bruno; Dionigi, Renzo; Spaggiari, Lorenzo; Foschi, Diego; Polvani, Gianluca; Orecchia, Roberto; Fazio, Nicola; Pravettoni, Gabriella; Cossu, Maria Laura; Galetta, Domenico; Venturino, Marco; et al.
Graphical abstract: Abstract: Cancer of the esophagus and of gastroesophageal junction can be cured, even if with lacking cure rate. Different approaches have been developed, mostly when carcinoma has loco-regional pattern. Multimodality therapy showed a survival rate superior than 10% if compared to a single approach. This is a systematic review, carried to assess the following matters: Which therapeutic opportunities are available? Who could benefit of them? Which adverse reactions could possibly verify? How can physicians definitely choose the proper strategy? Which is the role of surgery? We mean to give either General Practitioner or specialists clear and efficient updates about current treatment of this tumour, starting from physical examination. Four eminent guidelines were consulted for our study: Cancer Care Ontario's Program in Evidence-Based Care, NCCN, Belgian Health Care Knowledge Centre and Esmo.